Effect of green manure along with nitrogenous fertilizer on the growth and yield of turmeric (curcuma longa l.) of Bangladesh - Ferdous, Mahbuba; Kabirul Islam, Mohammad; Monirul Islam, Md.; Isfatuzzaman Bhuyan, Md; Sazedul Islam, Md; Sarkar, Purmendu (International Journal of Advanced Geosciences, 2018)
Turmeric is an important spice crop of Bangladesh. A field experiment was conducted at farmerâ€™s field of North Jhatibunia, Mirzagonj, Patuakhali during April, 2015 to February, 2016. The study was performed to find out the effect of green manure and nitrogenous fertilizer on the growth and yield of turmeric (BARI Halud-2), in coastal region of Bangladesh. In this study different combinations of green manure along with nitrogenous fertilizer were used. There was eight treatment combinations (viz. 7 ton biomass/ha + 100 kg N/ha, 7 ton biomass/ha + 80 kg N/ha, 7 ton biomass/ha + 60 kg N/ha, 7 ton biomass/ha + 40 kg N/ha, 7 ton biomass/ha + 20 kg N/ha, 7 ton biomass/ha, 100 kg N/ha and control). The highest number of leaves per plant (11.67) were recorded by the combined application of 7 ton biomass/ha along with 100 kg N/ha. The highest plant height (80.70 cm) and the longest leaf length (47.33 cm) were recorded by the application of 100 kg N/ha. The highest number of tillers per plant (7.67), maximum number of primary rhizomes per plant (9.00), maximum fresh weight of clump (189.67 g), highest fresh weight of roots (48.01 g), maximum fresh weight of rhizomes (277.70 g), maximum dry weight of clump (20.01 g), highest dry weight of roots (9.25 g), maximum dry weight of rhizomes (67.50 g) and maximum yield of fresh rhizome per hectare (6.64 tons) were recorded by the combined application of 7 ton /ha biomass+ 40 kg N/ha. Highest number of secondary rhizomes per plant (17.00) and maximum number of tertiary rhizomes per plant (7.00) were recorded by the application of 7 ton biomass/ha + 60 kg N/ha. With a few exception, the best performance in terms of growth and yield of turmeric were found from the combination of 7 ton biomass /ha + 40 kg N/ha.Â Â